EEG oscillations during caress‐like affective haptic elicitation. (20th May 2018) - Valenza, Gaetano; Greco, Alberto; Bianchi, Matteo; Nardelli, Mimma; Rossi, Simone; Scilingo, Enzo Pasquale
Abstract: Noninvasive, objective quantitative techniques to gauge emotional states are fundamental for clinical psychology as they overcome subjective bias of currently used questionnaires. To this end, we investigated brain oscillatory EEG activity during caresslike, affective haptic elicitation conveyed on the forearm at two force (strength of the caress) and three velocity (velocity of the caress) levels. Thirty‐two healthy subjects (16 female) were asked to assess each haptic stimulus in terms of arousal (i.e., intensity of emotional perception) and valence (i.e., pleasantness/unpleasantness of emotional perception) scores, according to the circumplex model of affect. Changes in brain oscillations were quantified through spectral and functional connectivity analyses. EEG power spectra were estimated through the individual α frequency peak. Results, expressed in terms of p ‐value topographic maps, revealed a suppression of α, β, and γ oscillations over the contralateral somatosensory cortex during unpleasant caresses performed with the lowest force (2 N) and the highest velocity (65 mm/s). Conversely, pleasant caresses at the highest force were associated with a significant decrease of EEG oscillatory activity over the midfrontal region, at frequency bands including α, β, and γ. A correlation analysis showed that EEG γ power from the somatosensory area was linked to caressing force. The more unpleasant the affective cutaneous stimuli, the more the brain dynamics decrease in activity all over the scalp, primarily showing a suppression of α power over the midfrontal cortex. These results also pave the way for the design of haptic systems eliciting a given emotional state.